The Impact of Organizational Culture on Ai Readiness in Customer Service: Evidence from Saudi Arabia - TULAİMAT, RUBA (İstanbul Kültür Üniversitesi, 2025)
This article examines the impact of artificial intelligence (AI) implementation on the culture within customer service organizations in commodity supply companies in Saudi Arabia. When companies rely on customer satisfaction and interpersonal communication for success, digital transformation initiatives often encounter challenges as individuals resist change and technology conflicts with existing practices. As AI technologies increasingly integrate into business, particularly in customer service positions, it's crucial to recognize the human and cultural influences that impact how individuals engage with AI. The General Attitudes toward Artificial Intelligence Scale (GAAIS) and the Perceived Support for Innovation (PSI) scale are two recognized measurement methods utilized in this study. These tools serve to determine how an organization's culture influences employees' mental readiness to engage with AI technologies. We employed a quantitative, cross-sectional research approach and collected 306 valid responses from individuals employed in diverse sectors, including retail, hospitality, manufacturing, import/export, and cottage food production. The questionnaire was translated into Arabic to ensure it was culturally and linguistically suitable. It was subsequently provided to a team of workers of varying ages, genders, and degrees of professional experience. The design enables us to examine how internal organizational dynamics, particularly the engagement of leadership and the receptiveness to new ideas, influence employee perceptions of AI in customer service.
Keywords: Artificial Intelligence; Organizational Culture; Customer Service; AI Readiness; Attitudes Toward AI